Traveling waves for a diffusive SEIR epidemic model with non-local reaction and with standard incidences. (October 2017) - Tian, Baochuan; Yuan, Rong
Abstract: This paper is devoted to the existence of the traveling waves of the equations describing a diffusive SEIR model with non-local reaction between the infected and the susceptible. The existence of traveling waves depends on the minimal speed c ∗ and basic reproduction rate β / γ . We use the Laplace transform and the Schauder fixed point theorem to get the existence and non-existence of traveling waves in our paper. We also give some numerical results of the minimal wave speed.